Maternal and neonatal outcome in second stage cesarean section versus first stage: a comparative study - S. R., Anusha; A. V., Deepak; Jacob, K. J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cesarean Section is the most commonly performed abdominal operation in women all over the world. Variable rates of cesarean section are reported between and within countries. Cesarean section at full cervical dilatation with an impacted fetal head can be technically difficult and is associated with increased trauma to the lower uterine segment and adjacent structures, as well as increased hemorrhage and infection. Methods: This is a comparative cross-sectional study comparing maternal and neonatal outcome between first stage and second stage cesarean section performed at Govt Medical College Thrissur. Results: In present study out of 90 cesarean sections 30 were performed in second stage and 60 in first stage.74 % were primigravida in second stage cs group. Arrest due to malposition was major indication for second stage (76% of cases). The most important complication among second stage cs group was PPH (76.7%) and majority of them needed blood transfusion. These complications were less in first stage cs group. Other Complications like increased duration of surgery (mean=53.3 min), post op fever (36% post op Wound infection (13.3%) was seen in second stage group. Fetal complications like low APGAR scores were seen in 16.7% of cases compared to first stage group and most of them needed resuscitation. Conclusions: Women undergoing cesarean section in second stage of labour had increased maternal and fetal morbidity. They required special care and hence Operation should ideally perform and supervised by an experienced obstetrician. Timely decision for cesarean section should be made especially when risk factors for failure to progress are present.